A study on the morphometric characteristics of Astacus leptodactylus inhabiting the Thrace region of Turkey - Deniz, T.; Harlioglu, M. M.; Deval, M. C. (Edp Sciences S A, 2010)
This study was carried out to determine some morphological characteristics, and the length-length and length-weight relationships of freshwater crayfish (A. leptodactylus Eschscholtz 1823) in the area of Tekirdag, in the Thrace region of Turkey. The total length and wet weight for all individuals ranged from 33 to 156 mm and 0.64 to 96.42 g, respectively. Although the average length of both sexes was nearly the same, the average weight of male crayfish was higher than that of females. The total length-wet weight relationships for males, females and combined sexes of wet weight were found to be: WW = 7.10(6)TL(3.293), WW = 2.10(5)TL(3.022) and WW = 9.10(6)TL(3.224), respectively. Isometric growth for female crayfish and positive allometric growth for male crayfish were observed in all populations. The carapace length, carapace width, and chela length and width increased allometrically with total length (TL) in both sexes. In conclusion, the morphometric relations in A. leptodactylus observed in the present study could provide information for future studies and management plans.
Keywords: crayfish; morphometric characters; length-weight relationship; allometric growth; Thrace region